Efektivitas Tontonan Edukasi Clash of Champions by Ruang Guru dalam Meningkatkan Motivasi Belajar Siswa di SMA Nergeri 1 Pedes - Giri Loviansyah; Arif Rahman Hakim; Holy Greata Singadimedja (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Learning motivation is one of the important factors that affected the success of the learning process and the learning outcomes of students. Learning motivation is influenced by what individuals usually do, one of the factors affecting learning motivation is educational videos. The aims of This study to examine the effectiveness of the educational spectacle Clash of Champions by Ruangguru in increasing the learning motivation of students of SMA Negeri 1 Pedes Karawang. The method used is a true experimental quantitative method with a Randomized Two-Group Pretest-Posttest design. The research participants were 40 grade X students that divided into experimental and control classes. Data were collected using a learning motivation scale from Gusmaninda et al (2024) which has been tested for validity and reliability, then analyzed by testing parametric statistics independent sample t test and paired sample t test. The results showed that the experimental class experienced a significant increase in learning motivation after the intervention, with a t = t-test 10.860) (p < 0.001) and an effect size of 28.54%. that meaning education videos Clash Of Champions By Ruang Guru giving impact 28.54% against the improvement of the experimental group.